How to Make Paper Planes - Robinson, Nick (UK, 2005)
In this excellent introduction to the art of paper-folding, there are step-by-step guides to making specially commissioned paper planes from the classic Keel Plane to the Acrobatic Barnstormer...
Keywords: Arts & Crafts; Juvenile Non-Fiction; Paper Planes